MULTIVARIATE STATISTICAL TECHNIQUES OF WATER QUALITY IN TIGRIS RIVER WITHIN BAGHDAD CITY - Noor Q. Ahmed; Karim R. Gubashi (Journal of Engineering and Sustainable Development, 2021)
This study was conducted to assess the water quality of Tigris River within Baghdad city by using Weighted Arithmetic model. The studay area included five sites: Thiraa-Tigris (S1), Al-Muthana bridge (S2), Al-Shuhadaa bridge (S3), Al-Doraa (S4) and confluence point of the Diyala river (S5). Ten water quality parameters were used in this study, Total Hardness (TH), Calcium (Ca), Hydrogen Ion concentration (pH), Chloride (Cl), Magnesium (Mg), Nitrate (NO3), Sodium (Na), Boron (B), Turbidity (TUR) and Sulfate (SO4). Statistical analysis such as correlation and regression coefficient using the statistical program SPSS was used to evaluate the results of the water quality index as well as to find a relationship between the water quality index and the variables. Several statistical methods, Factor Analysis (FA), Principal Component Analysis (PCA), Discriminant Analysis (DA), and Time Series Analysis assess parameters affecting water quality during the study period (August-December) 2019. The results showed Poor to Unsuitable quality index in Tigris River at Baghdad city except for Al-Muthna Bridge (S2) was grade good quality index during the time. From the analysis, that the worst water quality index was found at confluence place of Diyala River (S5) and grade unsuitable quality index.